Exploring stakeholder perceptions of facilitators and barriers to using needle exchange programs in Yunnan Province, China. - Morgan M Philbin (Public Library of Science (PLoS), 2014)
Injection drug use is an ongoing urban health crisis in China and one of the largest drivers of the transmission of HIV/AIDS. Sentinel surveillance sites in Yunnan province show upwards of 20% of injection drug users (IDUs) are HIV positive. Though the Ministry of Health has scaled-up needle exchange programs (NEPs), they have not received official government recognition nor have they been extensively evaluated to explore factors influencing their acceptability and feasibility. Using in-depth qualitative interviews conducted from February to July 2008 with 35 participants consisting of IDUs and other key stakeholders, we explored facilitators and barriers to accessing needle exchange programs in Kunming, the capital of Yunnan province. Content analysis was conducted to identify themes including attitudes toward NEPs and harm reduction, barriers to access, and suggestions for improvement. Themes that emerged included fears of breached confidentiality and police interference at the exchange sites and tensions between the public health and law enforcement perspective. Low levels of NEP-related knowledge and awareness were uniformly reported among interviewees. Suggestions to facilitate an increase in NEP acceptance included raising awareness of harm reduction and HIV more generally, offering services such as psychological counseling, job training and behavioral therapy at NEPs, and increasing communication between police, government, and public health officials. High rates of HIV infection among injection drug users in China have prompted rapid scale up of NEPs. Additional adaptations are necessary, however, to increase needle exchange use among injection drug users. This study finds that an urgent need to raise awareness of NEPs among policy makers and IDUs and act upon identified steps for developing social-structural interventions to create enabling environments that facilitate increased access to NEPs among injection drug users in Kunming.